Heavy is the Head That Wears the Crown: Black Men's Perspective on Harmful Effects of Black Women's Hair Product Use and Breast Cancer Risk. Issue 6 (November 2020) - Teteh, Dede K.; Chan, Marissa; Turner, Bing; Hedgeman, Brian; Ericson, Marissa; Clark, Phyllis; Mitchell, Eudora; Barrett, Emily; Llanos, Adana; Kittles, Rick; Montgomery, Susanne
Racial disparities in breast cancer are well-documented, and Black women assume a disproportionate burden of breast cancer mortality. Black women also commonly use hair products containing endocrine disrupting chemicals (EDCs) more often at an increased rate, as compared to other racial/ethnic groups. Emerging findings have reported the use of hair and other personal care products containing EDCs may contribute to breast cancer risk. While some sociocultural perspectives about hair and identity have been explored, the role of beauty expectations upheld by males has not been studied. Through a community-based participatory methodology, we explored perceptions and beliefs held by Black men regarding Black women's hair, chemical exposures in hair products, and breast cancer risk. Focus groups and key informant interviews—among men with and without partners with a history of breast cancer—were used to examine the male perspective regarding the attractiveness of Black hairstyles, opinions of beauty norms, and knowledge of breast cancer risk factors. Interviews were audio-recorded, transcribed, and analyzed guided by grounded theory methods. From the 66 participants interviewed, there was general support for natural hairstyles, which were associated with confidence and self-esteem in women. Men agreed that beauty standards and societal pressures play notable roles in the women's personal behaviors though they mostly lacked knowledge of women's breast cancer risk related to EDCs found in personal care products. Participants suggested a multipronged strategy centered on community education involving social and traditional media campaigns, and the engagement of policy makers in intervention efforts.